Rethinking Tourism Impact and Development on Local Community in Perlis, Malaysia - ABD RASHID, Intan Maizura; MOHD.YUSOF, Azman; ABU SAMAH, Irza Hanie; WAN HUSAIN, Wan Ahmad Fauzi; SHAFIAI, Syahiru; AMLUS, Mohammad Harith (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2020)
Tourism sector performance contributes to a large part of the Malaysian service economy (The World Factbook, 2013). In 2016, Malaysia faced an economic crisis, and it affects tourism sectors. Moreover, data from the Ministry of Tourism, Arts, and Culture (MOTAC) have shown that the number of tourists is decreasing at 1.5% in March 2016. This scenario has become a severe issue for the government because the Tourism Sector is one of the government’s important agenda in the NKEAs through National Ecotourism Plan. According to the MOTAC (2013), the nation's tourism sector is now the sixth-largest contributor to the national economy in 2014. However, inappropriate tourism development can lead to adverse social impacts. This research attempts to investigate the social impacts of tourism development on the local community in Perlis, Malaysia. Intends to develop and enhance its tourism sector to attract tourists to make the state as a stopover location. Even though Perlis records about 2.5 million tourists annually, most of them only pass through the state to continue their journey to Langkawi, Kuala Lumpur or Singapore. Nevertheless, studies are still lacking, particularly those speciﬁcally investigating the perception of local residents towards tourism development. The perception of the locals is important since it could determine the extent of their support for tourism development. Findings reveal that the residents understand the tourism sector could strengthen the national economy, but they also want natural resources to be protected.